PENGARUH EFEK EKSTRAK ETANOL DAUN SIRIH ( Piper Betle Linn.) SEBAGAI ANTIOKSIDAN TERHADAP LUKA BAKAR PADA KULIT PUNGGUNG KELINCI (Oryctolagus Cuniculus) - Muhammad Asri (As-Syifaa Jurnal Farmasi, 2017)
The burn are injuries to the skin where a response to the skin and subcutaneous tissue to the trauma experienced. The burn with partial thickness is a burn that does not damage the epithelial tissue of the skin and only damage some of the epithelial. This research aims to determine the effect of ethanol extract of betel leaf (Piper betle Linn.) As an antioxidant to burns on the skin back of the rabbit's (Oryctolagus Cuniculus). The experimental method was carried out experimentally, divided into 5 groups and treatment for 7 days, P1 negatife control (made wound on the skin back of rabbit and smeared with vaseline flavum), P2 positif control (made wound on rabbit’s skin back and smeared with bioplacenton ointment) P3 (made wound and ethanol extract of betel leaf with 5% concentration), P4 (made wound and ethanol extract of betel leaves with 10% concentration), P5 (made wound and ethanol extract of betel leaves with 15% concentration). The result of the research on the measurement of diameter of burn area on  rabbit's skin back before and after treatment, group I 2.5 cm and 2.4 cm, group II 2.5 cm and 1.9 cm, group III 2.2 cm and 1.9 cm, group IV 2.3 cm and 1.8 cm, and group V 2.3 cm and 1.6 cm. The conclusion of ethanol extract of betel leaf (Piper betle Linn) at concentrations of 5%, 10% and 15% as antioxidants can heal burns on the skin back of the rabbit's .